Computational Fluid Dynamic Modelling of Fully-Suspended Slurry Flows in Horizontal Pipes with Different Solids Concentrations - Messa, Gianandrea Vittorio (2023)
This research work is a significant step toward further understanding of the β-σ two-fluid model for the simulation of fully-suspended slurry flows in pipeline systems, with the goal of enhancing its potential for scientific research and engineering applications. Particularly, the focus of the study is the characterization and handling of the two main empirical coefficients of the model, namely, β and σ, which require case-specific tuning based on a given set of experimental data. Reference is made to the relevant case of slurry transport in horizontal pipes with infinite length. The influence of β and σ on different features of the fluid dynamic solution has been extensively investigated, considering also the role played by the specific testing conditions. Based on these findings, a procedure for determining appropriate values of β and σ has been developed, which requires only two experimental measurements, namely the concentration profile from a test at moderate slurry concentration, and the hydraulic gradient from another test in which the same slurry flows at high concentration. The procedure has been satisfactorily tested against published experimental data on pipe transport of fine glass bead and sand slurry.